Pengembangan E-Handout Berbasis Nearpod Materi Table Set Up sebagai Suplemen Pembelajaran bagi Siswa Fase F SMK Kuliner - Mardiyanti, Hanifah Saniinah; Widagdo, Andika Kuncoro; Astuti, Nugrahani; Miranti, Mauren Gita (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
The research and development (R&D) conducted aims to determine: 1) The results of the development of E-Handouts based on Nearpod material for Table Set Up. 2) The feasibility of E-Handouts based on Nearpod material for Table Set Up. 3) Student responses to teaching and learning activities using E-Handouts based on Nearpod material for Table Set Up. This research uses the ADDIE development model up to the fourth stage (Implementation) only or up to a limited trial. The feasibility of the E-Handout based on Nearpod material for Table Set Up is assessed through validation by subject matter experts using a Likert scale ranging from 1 to 4, validation by design experts using a Likert scale ranging from 1 to 5, and the collection of student response questionnaires using a Likert scale ranging from 1 to 5. The research subjects were 55 students from class XI at SMKN 2 Jombang. The results of this study indicate that: 1) The E-Handout based on Nearpod for the Table Set Up material can be accessed online. The results of the interactive e-handout are as follows: https://app.nearpod.com/?pin=A9RE3  .  2) The results of material and design feasibility showed an average material feasibility of 0.944 and an average media feasibility percentage of 0.950, indicating that they are highly feasible. 3) Student response results indicate very good criteria with an average of 85.04%. Thus, the Nearpod-based e-handout for table setup material developed in this study can be implemented in learning activities.